Financial globalisation dynamic thresholds for financial development: evidence from Africa - Simplice A. Asongu; Lieven De Moor (African Governance and Development Institute (AGDI), 2015)
Purpose - We investigate if financial development benefits from financial globalisation are questionable until certain thresholds of financial globalisation are attained. Design/methodology/approach - Financial globalisation is proxied with Net Foreign Direct Investment Inflows as a percentage of GDP (FDIgdp) whereas financial development entails dynamics of depth, efficiency, activity and size. The empirical evidence is based on; (i) data from 53 African countries for the period 2000-2011 and (ii) interactive Generalised Method of Moments with forward orthogonal deviations. Findings- The following findings are established. First, thresholds of FDIgdp from which financial globalisation increases money supply are 20.50 and 16.00 for below- and above-median sub-samples of financial globalisation respectively. Second, FDIgdp thresholds from which financial globalisation increases banking system activity and financial system activity for below-median sub-samples of financial globalisation are 13.81 and 13.29 respectively. Third, for financial size, there is evidence of: (i) a positive threshold of 21.30 in the full sample and (ii) consistent increasing returns without a modifying threshold for the above-median sub-sample. Practical implications- Evidence of a positive threshold implies that while the initial effect of financial globalisation on financial development is negative, there is a positive marginal effect, such that at a certain level of FDIgdp (or threshold), the overall effect of financial globalisation on the given financial development dynamic becomes positive. It follows that financial globalisation is both negative and positive for financial development, with a U-shaped relationship. Therefore the appropriate role of policy should neither be to stem the tide of capital flows nor to encourage them, but to understand what levels or thresholds of capital flows are required to benefit domestic financial development. Originality/value- We have extended the debate on initial or threshold conditions for the financial development benefits from financial globalisation by providing policy makers with levels of FDI (as percentage of GDP) that are required to start materialising financial development benefits from financial globalisation.
Keywords: F02; F21; F30; F40; O10; 330; Banking; International investment; Financial integration; Development